2010
DOI: 10.1038/gene.2010.29
|View full text |Cite|
|
Sign up to set email alerts
|

STAT4 is a confirmed genetic risk factor for Sjögren's syndrome and could be involved in type 1 interferon pathway signaling

Abstract: Signal transducer and activator of transcription 4 (STAT4) is a transcription factor mainly activated by interleukin 12, which promotes the secretion of type 2 interferon (IFN) by T-helper 1 cells. We assessed the association of STAT4 gene polymorphism and primary Sjö gren's syndrome (pSS) and its functional relevance. We analyzed STAT4 rs7582694 polymorphism in an exploratory cohort of 186 pSS patients and 152 controls, and in a replication cohort of 192 pSS patients and 483 controls, all Caucasian. mRNA leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 22 publications
(36 reference statements)
0
55
0
3
Order By: Relevance
“…The STAT4 gene encodes a transcription factor expressed on lymphocytes, macrophages, and dendritic cells and critical for interleukin-12 signaling, Th1 differentiation and production of interferon-c (INFc) [41]. Several investigators have confirmed associations between STAT4 variants and various AID especially with SLE [42][43][44][45]. It has also been shown that some variants of STAT4 were associated with different expression levels [46].…”
Section: Discussionmentioning
confidence: 97%
“…The STAT4 gene encodes a transcription factor expressed on lymphocytes, macrophages, and dendritic cells and critical for interleukin-12 signaling, Th1 differentiation and production of interferon-c (INFc) [41]. Several investigators have confirmed associations between STAT4 variants and various AID especially with SLE [42][43][44][45]. It has also been shown that some variants of STAT4 were associated with different expression levels [46].…”
Section: Discussionmentioning
confidence: 97%
“…An association between this polymorphism and high levels of IRF5 mRNA was demonstrated in PBMCs and in cultured salivary epithelial cells after viral infection ). STAT4 polymorphism was also associated with SS (Nordmark et al, 2009;Korman et al, 2008;Gestermann et al, 2010;Palomino-Morales et al, 2010). MECP2 and IL2-IL21 polymorphisms have also been associated with SS (Cobb et al, 2010;Maiti et al, 2010).…”
Section: Genetic Factors 331 Genetic Variationmentioning
confidence: 89%
“…An increasing body of evidence for the implication of other gene variants outside the HLA locus association is being put forth recently. Gene polymorphisms of IRF-5 and STAT-4 genes, two transcription factors of pivotal importance in interferon pathway, have been associated with various autoimmune diseases (Martinez et al, 2008), as well as with SS Korman et al, 2008;Miceli-Richard et al, 2009;Nordmark et al, 2009, Gestermann et al, 2010. The most significantly associated single nucleotide polymorphism (SNP) of the IRF5 gene was a 4 fold repetition, instead of three, of a sequence within the promoter region (Nordmark et al, 2009).…”
Section: Genetic Factors 331 Genetic Variationmentioning
confidence: 99%
“…Signal transducer and activator of transcription 4 (STAT4) is a ranscription factor mainly activated by interleukin 12, which promotes the secretion of type 2 interferon (IFN) by T-helper 1 cells [7].The STAT4 gene encodes a transcription factor belonging to the STAT family expressed in lymphocytes, macrophages, and dendritic cells. STAT4 is essential for interleukin (IL)-12 signaling and induces interferon-gamma (IFNγ) production and Th1 differentiation.…”
Section: Introduction:-mentioning
confidence: 99%